2009
DOI: 10.1103/physrevb.80.235111
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer splitting andc-axis coupling in bilayer manganites showing colossal magnetoresistance

Abstract: By performing angle-resolved photoemission spectroscopy of the bilayer colossal magnetoresistive ͑CMR͒ manganite, La 2−2x Sr 1+2x Mn 2 O 7 , we provide the complete mapping of the Fermi-level spectral weight topology. Clear and unambiguous bilayer splitting of the in-plane 3d x 2 −y 2 band, mapped throughout the Brillouin zone, and the full mapping of the 3d 3z 2 −r 2 band are reported. Peculiar doping and temperature dependencies of these bands imply that as transition from the ferromagnetic metallic phase ap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…For instance, high resolution experiments allowed resolving the coherent quasiparticle peaks and their renormalized dispersion at E F . 54,56 The ability to take this type of data efficiently allowed exploring a large phase space of temperature, momentum, and doping in our own study, 208 partly shown in Figure These results are quite promising and hint at the power of spin-resolved photoemission in addressing the physics in these materials. However they do not offer the level of data required to resolve the questions presented above.…”
Section: Cmr Manganitessupporting
confidence: 48%
“…For instance, high resolution experiments allowed resolving the coherent quasiparticle peaks and their renormalized dispersion at E F . 54,56 The ability to take this type of data efficiently allowed exploring a large phase space of temperature, momentum, and doping in our own study, 208 partly shown in Figure These results are quite promising and hint at the power of spin-resolved photoemission in addressing the physics in these materials. However they do not offer the level of data required to resolve the questions presented above.…”
Section: Cmr Manganitessupporting
confidence: 48%
“…1(b). As revealed by many theoretical and experimental studies, the two hole pockets arise from bonding and antibonding bands of bi-layer splitting band structure in this material with hybridized d x 2 −y 2 and d 3z 2 −r 2 states of e g electrons, and the outer electron pocket consists mainly of d 3z 2 −r 2 e g states151718192021. However, the inner electron pocket has not yet been explicitly presented by ARPES investigations.…”
Section: Resultsmentioning
confidence: 89%
“…This doping dependence is intriguing but potentially puzzling given such sensitivity. Still, work in other correlated electronic systems, such as the manganites, demonstrates that such a small doping change does cause a qualitative change in the electronic structure [44]. Thus, the IE has a strong sensitivity to optimal doping and, therefore, there exists a rapid change in the electron-lattice interaction near optimal doping.…”
Section: Isotope Effect In Arpes Width Of Bi2212mentioning
confidence: 99%